2016
DOI: 10.5005/jp-journals-10052-0058
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Comparative Evaluation of the Antibacterial and Antifungal Activities of Different Root Canal Sealers against Endodontic Pathogens

Abstract: Introduction: Elimination of microorganisms from the root canal and preventing them from reinfecting is the main objective of endodontic treatment. The sealers exhibit antimicrobial activity that may contribute to the elimination of intracanal microorganisms and the success of endodontic treatment. Aim: To evaluate the antibacterial and antifungal activities of different root canal sealers against endodontic pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Este cemento no libera formaldehído en su proceso de polimerización, mejorando así su biocompatibilidad, pero disminuyendo relativamente su actividad antimicrobiana. (Asawaworarit et al;Ramachandra et al, 2016). El cemento sellador a base de hidróxido de calcio (Sealer 26), obtiene su actividad antimicrobiana debido a la separación de los iones hidroxilo y calcio, alterando el gradiente de pH de la membrana citoplásmica microbiana, produciendo efectos como la desnaturalización de las proteínas, (por la elevada concentración de iones hidroxilo sobre las proteínas), biosíntesis de lípidos, daño del ADN y de la membrana citoplasmática microbiana (Pérez et al;Mohammadi et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este cemento no libera formaldehído en su proceso de polimerización, mejorando así su biocompatibilidad, pero disminuyendo relativamente su actividad antimicrobiana. (Asawaworarit et al;Ramachandra et al, 2016). El cemento sellador a base de hidróxido de calcio (Sealer 26), obtiene su actividad antimicrobiana debido a la separación de los iones hidroxilo y calcio, alterando el gradiente de pH de la membrana citoplásmica microbiana, produciendo efectos como la desnaturalización de las proteínas, (por la elevada concentración de iones hidroxilo sobre las proteínas), biosíntesis de lípidos, daño del ADN y de la membrana citoplasmática microbiana (Pérez et al;Mohammadi et al, 2011).…”
Section: Discussionunclassified
“…Se estima que el fracaso del tratamiento endodóntico puede alcanzar entre el 14 al 18% de los casos y puede ocurrir inclusive desde los seis meses post tratamiento y hasta luego de 10 años (Solanki et al, 2019). Su ocurrencia está asociada a una variedad de factores como la persistencia de bacterias (intracanal y extracanal), llenado inadecuado del canal, sobre extensión en la obturación, sellado coronal inadecuado, canales accesorios no tratados, diseño deficiente de la cavidad de acceso y complicaciones en la instrumentación (escalones, perforaciones o instrumentos separados) (Toledo et al, 2016;Tabassum & Khan, 2016;Yamaguchi et al, 2018).…”
Section: Introductionunclassified
“…After different periods of exposure, the zones of inhibition diameter were measured because the diffusion of a critical inhibitory concentration of the antibacterial agent into the agar media and the bacteria meeting a particular density were time related, altering the size of zone of inhibition. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Ramachandra et al . [ 11 ] have demonstrated that AH Plus sealer showed greater zone of inhibition for C. albicans than Enterococcus faecalis and Escherichia coli , whereas some studies concluded that AH Plus sealer had no antimicrobial action. [ 12 13 ]…”
Section: Discussionmentioning
confidence: 99%